Effectiveness of dragon fruit juice for glycemic control in elderly patients with type 2 diabetes mellitus - Sitanggang, Lastriana; Siagian, Masryna; Sibagariang, Eva Ellya (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a global health challenge with a rising prevalence, particularly among the elderly. Its management requires a holistic approach, including medical nutrition therapy. Red dragon fruit (Hylocereus polyrhizus) is rich in fibre and antioxidants, which may help regulate glucose metabolism. This study aimed to evaluate the efficacy of red dragon fruit juice on reducing random blood glucose levels in elderly patients with T2DM. Methods: A quasi-experimental study with a pretest-posttest control group design was employed. Thirty-two elderly T2DM patients within the working area of Karo District General Hospital were selected via purposive sampling and allocated into an intervention group (n=16) and a control group (n=16). The intervention group consumed 250 ml of red dragon fruit juice once daily for seven consecutive days, while the control group received routine care only. Random blood glucose levels were measured using a glucometer before and after the intervention. Data were analysed using descriptive statistics and the Wilcoxon Signed Ranks Test. Results: At baseline, the mean random blood glucose was 231.88 ± 99.37 mg/dL in the intervention group and 250.31 ± 63.32 mg/dL in the control group. Post-intervention, the intervention group exhibited a significant decrease to 226.25 ± 96.99 mg/dL (p=0.017). Conversely, the control group showed a non-significant increase to 252.75 ± 63.66 mg/dL (p=0.027). Rank analysis indicated that 75% of subjects in the intervention group experienced a decrease in blood glucose, whereas 81.25% of subjects in the control group experienced an increase. Conclusion: The administration of 250 ml of red dragon fruit juice daily for seven days was effective as an adjuvant therapy in reducing random blood glucose levels in elderly patients with Type 2 Diabetes Mellitus. Red dragon fruit may be considered a safe and affordable complementary nutritional intervention for T2DM management in the elderly population.